Analisis Pendekatan Contextual Teaching and Learning dengan Semangat Motivasi Belajar Pendidikan Agama Islam di SMP Al-Washliyah Muliorejo - Ahmad Khairuddin; Azmi Azmi; Asmayani Asmayani (MAN 4 Kota Pekanbaru, 2025)
This study aims to analyze the implementation of the Contextual Teaching and Learning (CTL) approach and its effect on students’ learning motivation in Islamic Religious Education (IRE) among ninth-grade students at Al-Washliyah Muliorejo Junior High School, Sunggal District. This study employed a quantitative approach. Data were collected through questionnaires measuring the CTL approach and students’ learning motivation, with a total of 38 respondents. Data analysis included normality, linearity, and homogeneity tests, followed by hypothesis testing using correlation and t-tests with the assistance of SPSS. The findings indicate that the CTL approach has a positive and significant effect on students’ learning motivation in Islamic Religious Education. The coefficient of determination indicates that the CTL approach contributes 60.5% to students’ learning motivation, while the remaining 39.5% is attributable to other factors. The t-test also demonstrates a significant effect, with a t-value of 14.969 and a significance value of 0.000, which is below the 0.05 significance level. These findings suggest that the implementation of the CTL approach can strengthen students’ learning motivation by connecting learning materials with students’ real-life experiences and contexts. Therefore, CTL can be considered an appropriate instructional approach for improving students’ engagement and motivation in Islamic Religious Education.